High prevalence of prehypertension in mothers of young children in peri-urban Nepal - Vaidya, Abhinav; Oli, Natalia; Krettek, Alexandra (Journal of Kathmandu Medical College, 2017)
Background: Prehypertension is clinically defined as a level of blood pressure between normal and hypertension, i.e. elevated systolic blood pressure between120-139 or diastolic blood pressure between 80-89 mm Hg. Prehypertension remains neglected as a public health problem, and has not been explored in mothers with small children in Nepal.Objectives: We aimed to study prehypertension and its related factors including obesity-related parameters among mothers with children aged 1-7 years in Duwakot and Jhaukhel communities of Bhaktapur district, Nepal.Methods: We prepared a sampling frame of all the eligible mothers, and interviewed 962 mothers. The trained enumerators also measured their blood pressure, body weight, height, waist and hip circumferences. We analysed data with SPSS version 22. We received ethical approval from the Nepal Health Research Council to conduct the study, and obtained informed verbal consent from the participating mothers.Results: About one-third (31.8%) of the mothers had prehypertension. It was more common among Newars and those aged 30-34 years. Multivariate analysis did not reveal significant association with socio demographic variables except for education. We found positive correlations between blood pressure and obesity parameters. Overweight and obese participants were 2.24 (95% confidence interval: 1.06-4.73) and 4.65 (95% confidence interval: 1.92-11.23) times, respectively, more likely to have prehypertension than underweight mothers.Conclusions: Our study demonstrated a high prevalence of prehypertension, coupled with high obesity parameters, among young mothers of peri-urban Nepal. Primordial preventive efforts at community level are needed not only for the mothers themselves, but for heart-health of their offspring as well.Journal of Kathmandu Medical CollegeVol. 5, No. 2, Issue 16, Apr.-Jun., 2016, page: 52-60